Persulphate Oxidation of Palm Oil Mill Effluent (POME):Post Treatment Process. - Chia, Ken Lin (2016)
The effectiveness of S2O8 2- oxidation and S2O8 2- /H2O2 oxidation as post treatment of POME were investigated. To the best of our knowledge, this is the first experimental study of S2O8 2- and S2O8 2- /H2O2 oxidations as treatment of biologically treated POME (BIOTPOME). The removal efficiencies of chemical oxygen demand (COD), ammoniacal nitrogen (NH3-N), colour and suspended solids (SS) were 36.8 %, 47.6 %, 57.7 % and 90.6 %, respectively by using S2O8 2- oxidation under certain operation conditions (S2O8 2- : CODi = 2.0 : 1.0, pH 11 and reaction time, 20 min). In S2O8 2- /H2O2 oxidation, 35.8 % COD, 75.8 % NH3-N, 87.8 % colour and 87.1 % SS were achieved in removal efficiencies under the operational conditions (S2O8 2- : CODi = 2.0 : 1.0, dosage of H2O2 / S2O8 2- = 2.45 g/1.63 g at pH 11 in 20 min contact time). For COD, the maximum removal efficiency obtained was 56.9 % in S2O8 2- /H2O2 oxidation (S2O8 2- : CODi = 2.0 : 1.0 and dosage of H2O2 / S2O8 2- = 2.45 g/1.63 g at pH 8.4 in 20 min reaction time). The study has proved that S2O8 2- /H2O2 oxidation have potentials in removing NH3-N of BIOTPOME under pH 11. However, the best COD removal was obtained at pH = 8.4.